2017
DOI: 10.1007/s10526-017-9816-x
|View full text |Cite
|
Sign up to set email alerts
|

Preventive application of an entomopathogenic fungus in cover crops for wireworm control

Abstract: Efficacy of the Metarhizium brunneum Petch (Hypocreales: Clavicipitaceae) strain ART2825 for control of wireworms (Agriotes obscurus (L.), Coleoptera: Elateridae) was examined in a semi-field pot experiment. Pots were treated in late summer during sowing of spring oat as a cover crop. Survival of wireworms was assessed four weeks after their release in October 2013, and 30 weeks after release in April 2014. Viability and persistence of the fungus was determined by counting colony forming units from substrate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 44 publications
0
19
0
2
Order By: Relevance
“…In particular, entomopathogenic fungi have gained importance within the entomopathogenic microorganisms mainly due to their unique contact mode of action through the cuticle (Quesada-Moraga and Santiago-Álvarez, 2008 ). Besides entomopathogenic fungi are naturally distributed in a wide range of habitats and the soil is considered their natural reservoir (Quesada-Moraga et al, 2007 ; Pell et al, 2010 ; Garrido-Jurado et al, 2015 ); therefore, soil application of entomopathogenic fungi to target soil dwelling stages of insect pests could be a powerful and sustainable pest management strategy (Rogge et al, 2017 ). Yousef et al ( 2017 ) have demonstrated the efficacy of soil treatments under olive tree canopy using the M. brunneum EAMa 01/58-Su strain (hereafter referred to as M. brunneum ) for B. oleae control, as well as the compatibility of M. brunneum with commercial herbicides under laboratory conditions (Yousef et al, 2015 ), while Garrido-Jurado et al ( 2011a ) have demonstrated the lack of negative direct or indirect impact of such treatments on the olive crop soil-dwelling non-target arthropod population.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, entomopathogenic fungi have gained importance within the entomopathogenic microorganisms mainly due to their unique contact mode of action through the cuticle (Quesada-Moraga and Santiago-Álvarez, 2008 ). Besides entomopathogenic fungi are naturally distributed in a wide range of habitats and the soil is considered their natural reservoir (Quesada-Moraga et al, 2007 ; Pell et al, 2010 ; Garrido-Jurado et al, 2015 ); therefore, soil application of entomopathogenic fungi to target soil dwelling stages of insect pests could be a powerful and sustainable pest management strategy (Rogge et al, 2017 ). Yousef et al ( 2017 ) have demonstrated the efficacy of soil treatments under olive tree canopy using the M. brunneum EAMa 01/58-Su strain (hereafter referred to as M. brunneum ) for B. oleae control, as well as the compatibility of M. brunneum with commercial herbicides under laboratory conditions (Yousef et al, 2015 ), while Garrido-Jurado et al ( 2011a ) have demonstrated the lack of negative direct or indirect impact of such treatments on the olive crop soil-dwelling non-target arthropod population.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, wireworms are also important potato pests in Europe. The suppression of wireworms in arable land is usually influenced by a limited number of insecticides, while knowledge of alternative methods for their suppression is usually insufficient (Ritter, Richter, 2013;Sufyan et al, 2013;Rogge et al, 2017). Several alternative plant protection methods can be used for the suppression of organisms that are harmful to potatoes.…”
Section: Introductionmentioning
confidence: 99%
“…At present, seed treatment with neonicotinoids (e.g., imidacloprid, clothianidin and thiamethoxam) is the most common approach for managing wireworms in cereal crops but this approach is inadequate and mainly works as a temporary preventive repellent (Vernon, ). Biological control agents, especially entomopathogenic fungi, can work alone or in conjunction with seed treatments (Ericsson, Kabaluk, Goettel, & Myers, ; Ester & Huiting, ; Jansson & Seal, ; Rogge, Mayerhofer, Enkerli, Bacher, & Grabenweger, ). Strains of several entomophagous fungi ( Metarhizium anisopliae F52, Metarhizium brunneum F52, Metarhizium robertsii DWR 346 and Beauveria bassiana ) kill wireworms and can control wireworms in grain and pulse crops in the north‐western USA (Antwi, Shrestha, Reddy, & Jaronski, ; Reddy et al, ; Tharp, Blodgett, & Jaronski, ).…”
Section: Introductionmentioning
confidence: 99%